2021
DOI: 10.1001/jamanetworkopen.2020.32086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of All-Cause Mortality Rates and Inequities Between Black and White Populations Across the 30 Most Populous US Cities

Abstract: Key Points Question How do all-cause mortality rates and racial inequities in rates vary across the 30 most populous US cities? Findings In this cross-sectional study of more than 26 million death records during a 10-year period, city mortality rates differed widely as did inequities between Black and White populations. Overall mortality rates improved in less than half of the 30 cities, and racial inequities worsened in more cities than in which they impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Foremost among these root causes is systemic racism; extensive research has shown that systems of power in the US structure opportunity and assign value in ways that unfairly disadvantage Black, Hispanic, Asian, and Indigenous populations, and unfairly advantage White people. 69 70 71 72 73 74 75 Many of the same factors placed these populations at greater risk from covid-19. 13 14 15 76 77 78 79 80 The higher prevalence of comorbid conditions in many racial or marginalized groups is a reflection of unequal access to the social determinants of health (eg, education, income, and justice) and not their race, ethnicity, or other socially determined constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foremost among these root causes is systemic racism; extensive research has shown that systems of power in the US structure opportunity and assign value in ways that unfairly disadvantage Black, Hispanic, Asian, and Indigenous populations, and unfairly advantage White people. 69 70 71 72 73 74 75 Many of the same factors placed these populations at greater risk from covid-19. 13 14 15 76 77 78 79 80 The higher prevalence of comorbid conditions in many racial or marginalized groups is a reflection of unequal access to the social determinants of health (eg, education, income, and justice) and not their race, ethnicity, or other socially determined constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of disproportionate reductions in life expectancy among racial and ethnic groups in the US, such as the disparities reported here, draws attention to the root causes of racial inequities in health, wealth, and wellbeing. Foremost among these root causes is systemic racism; extensive research has shown that systems of power in the US structure opportunity and assign value in ways that unfairly disadvantage Black, Hispanic, Asian, and Indigenous populations, and unfairly advantage White people 69707172737475. Many of the same factors placed these populations at greater risk from covid-19 1314157677787980.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that social inequities explain mortality rates in a wide range of diseases [12,32]. In the case of COVID-19, some studies suggest an increased risk of infection by SARS-CoV-2 among social groups characterised by vulnerability factors [33,34] and an increase in the lethality of the disease [35].…”
Section: Introductionmentioning
confidence: 99%
“…28−30 Specific examples of downstream racial inequities from bias are observed in provision of pain control, infant mortality rates, misdiagnosis rates, among many other clinical outcomes, including importantly all-cause mortality. 17,22,31,32 It remains unsurprising that the healthcare community has failed to earn the trust of BIPOC patients despite physicians being a highly trusted resource in general. 22,24,33…”
Section: Law Enforcement Violence Represents Only One Aspect Of Systemic Racismmentioning
confidence: 99%